Balanced Scorecard Analysis (BSC) for Performance Measurement at PT. Kompas Gramedia Circulation - Ramadina; Ritha Z. Tarigan (Journal of Economics and Business (JECOMBI), 2021)
The purpose of this study is to demonstrate the design of the Balanced Scorecard in the largest daily newspaper company in eastern Indonesia and to describe the causal relationship of strategic objectives on the Strategy Map to achieve the company's vision and mission. This research uses a qualitative case study approach. Data obtained by semi-structured interviews from several informants related to the preparation of strategic objectives in daily newspaper companies. The formulation of strategic objectives is identified through the elaboration of the vision and mission of PT. SKG. After that, the identified strategic objectives are defined into the Balanced Scorecard. The author uses the SKG daily newspaper company because PT.SKG does not have a framework that links the strategic objectives according to the vision and mission of PT.SKG. The results of this study indicate that the balanced scorecard design at PT.SKG produces 14 strategic objectives. The customer perspective has 2 strategic objectives. The strategic goal setting from the perspective in the Balanced Scorecard is appropriate and in line with the company's vision and mission. The flow of the cause and effect relationship with the company's strategic objectives is contained in the Strategy Map.